(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Red cell alloimmunisation in pregnancy may result in haemolytic disease of the foetus and newborn (HDN). During pregnancy, there are possibilities of the foetal antigen being exposed to the mother’s circulation, thereby leading to the production of antibodies. The immunoglobulin G (IgG) antibodies from the mother pass through the maternal surface placenta, which is then sensitised and obstructs the formation of foetal red blood cells (RBCs). This review discusses the presence of variance alloantibodies during pregnancy, as well as the consequences of HDN and its management. This review revealed that ABO incompatibility is the most common cause of alloimmunisation in pregnancy. The Rh system (anti-D and -E) are the most common alloantibodies found in pregnant women, followed by other alloantibodies such as Kell, Duffy, Kidd and MNSs. Hyperbilirunemia (increased bilirubin levels) is commonly seen in neonatal jaundice due to HDN and it is usually manageable using the phototherapy method. Nevertheless, the clinical significance of alloantibodies can cause complications such as anaemia, and in some extreme cases, kernicterus might require a blood exchange transfusion.